EU Food Law : Protecting Consumers and Health in a Common Market. - MacMaolin, Caoimhn (Modern studies in European law., 2007)
This is the first comprehensive analysis of the European Union law of food regulation. It details the way in which EU law impacts upon the production and sale of food throughout the Union. It examines the legal protection accorded to the free movement of food within the EU, discussing those circumstances in which Member States may derogate from this principle, in particular where this is done to protect human health or safeguard consumer interests. Chapter four discusses and places in context the international trade law influences on EU food law. Chapter five describes EU responses to recent f.